PRE-SERVICE TEACHERS’ DIGITAL LITERACY: A LEAP IN TIME (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2020)
Technology provides convenience in every aspect of life. In education, technology revitalizes and supports learning by breaking barriers which inhibits learning. Pre-service teachers are a key factor in future generation education, but their ability to make use of benefits technology has to offer is scarcely explored. In this qualitative study, we surveyed 480 students currently enrolled in one of Teachers Training Institutes in Indonesia and digital literacy in every undergraduate level (freshman, sophomore, junior, and senior) was evaluated. Substantial evidence was found and showed that digital literacy improves with education level. Implications for pre-service teachers’ education program are addressed.
Keywords: Pre Service Teacher; Digital Literacy; Competency Framework For Teachers